Development of a web-based virtual simulated learning environment for pharmacy practice education - Arash Najimi; Shirinsadat Badri; Mahdiyeh Azizkhani; Samaneh Zolghadr; Shaghayegh Roofeh; Sayyed Ali Sepehr; Sajjad Mohammadi (Wolters Kluwer Medknow Publications, 2022)
Objective: In the present study, we aimed to develop a virtual simulation that allows pharmacy students to play through actual prescriptions and pharmacy practice scenarios productively and on a personal computer. If designed properly, this program may serve as a supplementary educational tool without the need for an existing human tutor that could provide learning outcomes as good as those resulting from traditional paper-based pharmacy practice tutorials. Methods: A computer-based simulation of a community pharmacy was developed. This program mainly targeted three basic learning needs of pharmacy students: drug dispensing, patient counseling, and dealing with clinical situations related to the patients' prescription or demand for over-the-counter (OTC) recommendations. Fundamental design decisions were based on breaking down the dispensing process into logical components to provide discrete development elements. For teaching patient counseling and clinical skills, instructors wrote scenarios covering the most prevalent pharmacy practice issues, mainly focused on medication use during pregnancy or lactation, OTC recommendations, information related to drug interactions and adverse drug reactions, and interactions between prescription drugs and patient's underlying disease. Findings: Based on the primary curriculum topics, the development team designed exercises for pharmacy practice units presented to year 5 pharmacy students. Accordingly, exercises were developed to authentically reflect tasks and challenges a community pharmacist would regularly face in the workplace. To fulfill this part, over 2000 real prescriptions were scanned and categorized based on the main drugs included. These prescriptions were used for both activities, namely medication dispensing and clinical scenarios. Furthermore, five senior pharmacy students wrote more than 200 clinical scenarios under a clinical pharmacist's supervision. The main objectives of pharmacy practice courses were followed to cover the most important must-to-know clinical tips, whether related to giving relevant advice as an OTC recommendation, referring the patient to a primary care physician, or just providing a piece of general health advice, which is expected to be comprehensively learned by pharmacy students. Conclusion: This program was designed as a simulated learning environment to help students develop prescription dispensing and clinical skills. To be considered a success, this simulation needed to provide equivalent or better learning outcomes than the current practice approach, which should be assessed in the future evaluation of the software, and then be promoted accordingly.